2002
DOI: 10.1080/02650487.2002.11104939
|View full text |Cite
|
Sign up to set email alerts
|

Wireless digital advertising: nature and implications

Abstract: The convergence of the Internet and wireless telecommunications in the late 1990s has opened the way for a plethora of data services for the mobile handset user. One potential area of development is wireless advertising. The personal, always-at-hand nature of devices, along with the ability to assess context dependence (e.g. time and location), presents a rich platform for wireless advertising. Using a range of wireless platforms, operators will be able to offer very different advertising services that go beyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 14 publications
0
86
0
10
Order By: Relevance
“…Similarly, sporadic industry surveys report a rather optimistic blueprint. For example, an experimental survey conducted by Ericsson indicates that 60% of consumers liked receiving mobile advertising, while Quios finds that the level of recognition of mobile advertising was surprisingly high: 79% of participants recalled 60% of the advertising (Barnes, 2002).…”
Section: Sms Advertisingmentioning
confidence: 99%
“…Similarly, sporadic industry surveys report a rather optimistic blueprint. For example, an experimental survey conducted by Ericsson indicates that 60% of consumers liked receiving mobile advertising, while Quios finds that the level of recognition of mobile advertising was surprisingly high: 79% of participants recalled 60% of the advertising (Barnes, 2002).…”
Section: Sms Advertisingmentioning
confidence: 99%
“…Other intended consumer reactions to mobile advertising messages include following a link to a Web page, e-mailing the advertiser, purchasing a product, and placing a telephone call [93]. Compared to click-through rates of less than 1% for Web-based advertising [89], average clickand call-through rates for wireless devices are 19% and 12%, respectively [89].…”
Section: Common Applicationsmentioning
confidence: 99%
“…In addition, firms using mobile e-mail campaigns can attract consumer attention and produce consumer responses to a much greater degree than other direct marketing channels, because such firms can engage in "one-to-one dialogue" with customers (Kavassalis et al, 2003). An experimental survey by Ericsson indicates that 60 per cent of samples liked receiving mobile advertising (Barnes, 2003). Similarly, a survey using popular brands' trial mobile advertising found that as many as 84 per cent of 500 young British adults are likely to recommend the service to their friends, while only 7 per cent are likely to abandon the service (Barwise and Strong, 2002).…”
Section: Branding Strategymentioning
confidence: 99%
“…An earlier pilot study conducted by Quios found that in mobile advertising the level of recognition was surprisingly high: 79 per cent of participants recalled 60 per cent of mobile advertising (Barnes, 2003). In addition, firms using mobile e-mail campaigns can attract consumer attention and produce consumer responses to a much greater degree than other direct marketing channels, because such firms can engage in "one-to-one dialogue" with customers (Kavassalis et al, 2003).…”
Section: Branding Strategymentioning
confidence: 99%